PSYCHOANALYSIS OF RILEY CHARACTER IN THE DISNEY MOVIE “INSIDE OUT” - Sistha, Cantika Widya; Nur, Riola Haya; Fitriyani, Fitriyani (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study intends to look into the psychological traits that Riley, Joy, and Sadness—the three main characters from the film